Development of a mathematical model of dependence of specific volumetric electrical resistance of SIW-4 insulation on factors affecting its reliability - Denisov I. V. (Vestnik MGTU)
Insulation of self-supporting insulated wire (SIW-4) is the object of the study, and the subject of the study is a mathematical model of the dependence of the specific volume electrical resistance of the SIW-4 insulation on the factors affecting its reliability. The resulting mathematical model will allow us to proceed to the development of a method for predictive assessment of the residual life of the insulation material of the conductor under study. At the first stage of the work, the influence of external factors on the electrical parameters of the SIW-4 insulation material has been studied. When forming the goal of the study, namely, obtaining a mathematical model of the dependence of the specific volume resistance of the wire insulation on the influence of external factors, difficult operating conditions have been taken into account. SIW-4 is intended for use outside buildings, i. e. it is exposed to solar radiation, wind load, precipitation, temperature changes, etc. Within the framework of this study, the following most significant factors have been considered: alternating electric current, ambient temperature and period of operation. These factors have been selected taking into account the possibility of conducting a multifactorial experiment and fully characterize such properties of product reliability as durability and failure-free operation. During the multifactorial analysis, the task was to select the minimum and maximum values of each factor under study, followed by the compilation of a planning matrix for a full factorial experiment. The resulting mathematical model allows us to determine the effective value of the specific volume electrical resistance of the SIW-4 insulation material depending on its operation under the given specific conditions. It also opens up the possibility of developing the second stage of the study, associated with the construction of an algorithm for the method of predictive assessment of the residual life of the insulation material of the conductor under study.